CYP2C9*3/*3 Gene Expression Affects the Total and Free Concentrations of Valproic Acid in Pediatric Patients with Epilepsy - Wu X; Dong W; Li H; Yang X; Jin Y; Zhang Z; Jiang Y (Dove Medical Press, 2021)
Xikun Wu,1 Weichong Dong,1 Haoran Li,1 Xiuling Yang,1 Yiran Jin,1 Zhiqing Zhang,1 Ye Jiang2 1The Second Hospital of Hebei Medical University, Shijiazhuang City, People’s Republic of China; 2Pharmacy College, Hebei Medical University, Shijiazhuang City, People’s Republic of ChinaCorrespondence: Zhiqing ZhangThe Second Hospital of Hebei Medical University, Department of Pharmacy, 215 Hepingxi Road, Shijiazhuang City, 050000, People’s Republic of ChinaEmail 777yyy@sina.cnYe JiangPharmacy College, Hebei Medical University, 361 Zhangshandong Road, Shijiazhuang City, 050017, People’s Republic of ChinaEmail jiangye@hebmu.edu.cnPurpose: To perform therapeutic drug monitoring (TDM) of total and free plasma valproic acid (VPA) concentrations in pediatric patients with epilepsy and to analyze related factors.Patients and Methods: Pediatric epileptic patients treated in 2015– 2019 in our hospital were assessed. Total and free plasma VPA concentrations were obtained by UPLC and LC-MS/MS, respectively. Regression analysis was performed to examine the associations of free plasma VPA with total plasma VPA and plasma protein binding rate. The impacts of individual situation, CYP2C9 genotype, and drug combination on VPA concentration were examined.Results: Of the 251 patients, 81 had lower total concentrations than effective therapeutic levels; 86 and 31 patients had infections and central nervous system dysplasia, respectively. VPA’s daily doses and free drug concentrations were significantly lower in the CYP2C9 *3/*3 genotype group versus the CYP2C9 *1/*3 and CYP2C9 *1/*1 groups (P< 0.05). Free and total VPA concentrations were linked by Y = 0.0004 X2 + 0.042 X + 0.3035 (r=0.6981); VPA plasma protein binding rate and free VPA concentration were related by Y = 0.0003 X2 - 0.0127 X + 0.9777 (r=0.8136). Both total and free VPA concentrations were significantly decreased in patients simultaneously administered phenobarbital, meropenem and biapenem (P< 0.05), with therapeutic failure after meropenem/biapenem co-administration.Conclusion: Free VPA amounts have nonlinear relationships with total VPA amounts and plasma protein binding rate in epileptic children. Additionally, CYP2C9 *3/*3 expression affects VPA metabolism. Since phenobarbital affects VPA metabolism, TDM is recommended. Meanwhile, carbapenem-co-administration with VPA should be prohibited.Keywords: valproic acid, pediatric patient, free concentration, CYP2C9 gene expression, TDM